2020
DOI: 10.1186/s12881-020-0973-x
|View full text |Cite
|
Sign up to set email alerts
|

Prune belly syndrome in surviving males can be caused by Hemizygous missense mutations in the X-linked Filamin A gene

Abstract: Background: Prune belly syndrome (PBS) is a rare, multi-system congenital myopathy primarily affecting males that is poorly described genetically. Phenotypically, its morbidity spans from mild to lethal, however, all isolated PBS cases manifest three cardinal pathological features: 1) wrinkled flaccid ventral abdominal wall with skeletal muscle deficiency, 2) urinary tract dilation with poorly contractile smooth muscle, and 3) intra-abdominal undescended testes. Despite evidence for a genetic basis, previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 89 publications
0
12
1
2
Order By: Relevance
“…Murray et al documented the deletion of HNF-1 β gene on chromosome 17 in a patient with PBS ( 18 ). Iqbal et al reported on PBS patients with mutations of X-linked filamin A gene ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Murray et al documented the deletion of HNF-1 β gene on chromosome 17 in a patient with PBS ( 18 ). Iqbal et al reported on PBS patients with mutations of X-linked filamin A gene ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 En otro estudio se identificaron tres mutaciones del gen FLNA, implicado en la producción de la proteína filamina A, la cual regula la reticulación de actina que funciona en las células del músculo liso. 9 Además, se han propuesto teorías que implican alteraciones en diversas proteínas de contractilidad muscular visceral como resultado de mutaciones genéticas, incluyendo los genes ACTA2, ACTG2, MYH11, MYLK, MYOCD y HNF1B. 6 El diagnóstico precoz permite un tratamiento oportuno.…”
Section: Discussionunclassified
“…Algunas incluyen el origen genético heterogéneo, con la implicación de diversas proteínas de contractilidad muscular visceral o de alteraciones de los receptores muscarínicos colinérgicos M3, 6,7 o bien, que el modo de herencia está ligado al cromosoma X. 8,9 Otra propuesta describe que hay alteración en el desarrollo del mesodermo, lo cual explicaría las alteraciones morfológicas a nivel genitourinario, gastrointestinal y de otros sistemas. 10 El diagnóstico puede realizarse durante la gestación, a través de una ecografía obstétrica con evidencia de contornos irregulares en el abdomen asociado con un aumento de su circunferencia, anomalías del tracto urinario, oligohidramnios, ascitis fetal y uraco permeable.…”
unclassified
“…Nevertheless, this field of genomic investigation of human urinary tract malformations is rapidly expanding, with variants in yet other genes reported every few months by research laboratories. Recent examples are: BNC2 [23], encoding the protein basonuclin 2 expressed in the urogenital sinus, with mutations causing urethral obstruction; FLNA, encoding filamin A, an actin crosslinking protein expressed in bladder smooth muscle and mutated in some cases of prune belly-like syndrome [24]; SLC20A1 [25], coding for sodium-dependent phosphate transporter 1 expressed in and around the urogenital sinus, with mutations associated with bladder extrophy; and EBF3, coding for the early B cell factor 3 transcription factor that when mutated causes dysfunctional voiding [26]. Probably, there will be many other genes implicated in this group of diseases and, as genetic testing becomes more widely adopted in the clinic, a greater proportion of all individuals with urinary tract malformations will be found to have a genetic cause.…”
Section: Clinical Impact Of Urinary Tract Malformationsmentioning
confidence: 99%